Achieving an optimal group structure in a neural architecture search. Issue 19 (28th July 2022) - Seo, W.; Park, J.; Lim, W.; Kim, D.; Lee, J.
Abstract: The method proposed in this letter searches for an effective group structure of group convolutions in a convolutional neural network that can improve the classification accuracy. The model's group structure is obtained using an effective differential neural architecture search. Our code can be accessed at https://github.com/minercode625/grunas.git .